Peran dan Usaha Pesantren dalam Pemberdayaan Masyarakat - Sanusi, M.; Anshory, Muhammad Isa (TSAQOFAH, 2024)
This article discusses the role of Islamic boarding schools in community empowerment efforts in various fields. The aim is to find out the extent of the role and business of Islamic boarding schools in community empowerment efforts. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The presence of Islamic boarding schools in various regions plays a very active role in community empowerment efforts in various fields, both social, educational and economic, which also develop along with the development of Islamic boarding schools in these areas.